Beckett and Eros - Davies, P. author. aut Link
IX, 239 p.
Keywords: The decade since Beckett's death has seen new interests in the erotic sweeping through our culture, acting in uneasy counterpoint to its established humanistic infrastructure and opening new questions about the significance of sexuality. Surprisingly or not, Beckett has startling further light to throw on the erotic phenomenon variously but insistently recognised in our time. This book is the first to propose a 'mythopoetics of sex' with which to explore Beckett's work as a whole.